Game-Theoretical Modeling of Interviral Conflicts Mediated by Mini-CRISPR Arrays - Iranzo, Jaime; Faure, Guilhem; Wolf, Yuri I.; Koonin, Eugene V. (Frontiers in Microbiology, 2020)
All cellular organisms coevolve with multiple viruses, so that both virus-host and intervirus conflicts are major factors of evolution. Accordingly, hosts evolve multiple, elaborate defense systems and viruses respond by evolving means of antidefense. Although less thoroughly characterized, several dedicated mechanisms of intervirus competition have been described as well. Recently, the genomes of some bacterial and archaeal viruses have been shown to harbor CRISPR mini-arrays that typically contain a single spacer targeting a closely related virus. The involvement of mini-arrays in an intervirus conflict has been experimentally demonstrated for a pair of archaeal viruses. We model the evolution of virus-encoded CRISPR mini-arrays using a game theoretical approach. Analysis of the model reveals multiple equilibria that include mutual targeting, unidirectional targeting, no targeting, cyclic polymorphism, and bistability. The choice between these evolutionary regimes depends on the model parameters including the coinfection frequency, differential productivity of the conflicting viruses, and the fitness cost of mini-arrays. At high coinfection frequencies, the model becomes a version of the Prisoner’s dilemma in which defection, i.e., mutual targeting between the competing viruses, is the winning strategy.